1980
DOI: 10.3928/0147-7447-19800901-12
|View full text |Cite
|
Sign up to set email alerts
|

Vastus Medialis Oblique: An Anatomic and Physiologic Study

Abstract: The lower part of the vastus medialis, which originates chiefly from the tendon of the adductor magnus, has been designated as the "vastus medialis oblique." This muscle is peculiar to man. The fibers of the muscle are mostly horizontal; therefore they are in a unique position to stabilize the patella against the femur in the later stages of extension of the knee. This article details the anatomic and physiologic features of the vastus medialis oblique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(13 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Although hamstrings tension affects the kinematics [18], we felt that it was not practical to add an investigation of their effects to an already long experimental protocol, because of our concern about deterioration of the specimens. Previous works on knee extension have shown the importance of the oblique components of the quadriceps [4] and using multiplanar loading directions on patellar mechanics [25]. Although the individual heads of the quadriceps were tensioned in a physiological ratio, their overall tension was limited by tearing the muscle fibres in these elderly specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Although hamstrings tension affects the kinematics [18], we felt that it was not practical to add an investigation of their effects to an already long experimental protocol, because of our concern about deterioration of the specimens. Previous works on knee extension have shown the importance of the oblique components of the quadriceps [4] and using multiplanar loading directions on patellar mechanics [25]. Although the individual heads of the quadriceps were tensioned in a physiological ratio, their overall tension was limited by tearing the muscle fibres in these elderly specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors maintain that the primary role of VMO is to enhance patellar stabilization within the patello‐femoral joint and to prevent lateral patellar subluxation by pulling the patella medially during knee extension and flexion [24, 43, 46, 58]. More than 50 years ago, Brewerton [8], followed by Lieb and Perry [40], Martin and Londeree [44], and Bose et al [7], reported VMO to be active during the full range of knee extension. Mariani et al [43] found the EMG activity of both VM and VL to be of similar degree and mostly pronounced during the last 30° of knee extension in healthy subjects.…”
Section: Clinical Examinationmentioning
confidence: 99%
“…In the past 20 years, our understanding of the medial patellofemoral complex has evolved significantly. 5,14,15,27 The MPFL was originally described as an aspect of the medial retinaculum connecting the vastus medialis to the adductor tubercle and subsequently named by Warren and Marshall 35 in 1979. Conlan et al 8 described the role of this medial soft tissue restraint in inhibiting lateral patellar displacement.…”
Section: Discussionmentioning
confidence: 99%